Prof. Hecheng Li: focusing on clinical research to provide more data support for robotic surgery - Yuan, Amber (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
The 3rd Ruijin International Thoracic Surgery Symposium was successfully held in Shanghai from 15th to 16th of November in 2018, gathering many renowned experts and scholars from the frontier field at home and abroad to discuss the latest progress and hot issues in thoracic surgery.